2021
DOI: 10.1183/13993003.04445-2020
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of severe community-acquired staphylococcal pneumonia in France

Abstract: PurposeStaphylococcus aureus causes severe forms of community-acquired pneumonia (CAP), namely staphylococcal pleuropneumonia in young children and staphylococcal necrotising pneumonia in older patients. Methicillin resistance, the Panton-Valentine leukocidin (PVL) toxin, as well as less specific factors have been associated with poor outcome in severe CAP, but their respective roles are unclear.MethodsA prospective multicentre cohort study of severe staphylococcal CAP was conducted in 77 paediatric and adult … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 40 publications
(49 reference statements)
2
40
1
1
Order By: Relevance
“…Clinical isolates and accompanying clinical data were obtained from a previously published French cohort of severe CAP [15]. The clinical features retained for the present study were those representing severity and outcome in the cohort study: death, leukopenia (defined as total leukocyte count < 3 G/L), and hemoptysis extracted from the Gillet study [15] (Table S2). The age-adapted Charlson Comorbidity Index (CCI) score was retained as a control covariate to adjust prediction models to the baseline characteristics of the patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical isolates and accompanying clinical data were obtained from a previously published French cohort of severe CAP [15]. The clinical features retained for the present study were those representing severity and outcome in the cohort study: death, leukopenia (defined as total leukocyte count < 3 G/L), and hemoptysis extracted from the Gillet study [15] (Table S2). The age-adapted Charlson Comorbidity Index (CCI) score was retained as a control covariate to adjust prediction models to the baseline characteristics of the patients.…”
Section: Methodsmentioning
confidence: 99%
“…Given the large diversity in the genetic background of the corresponding strains ( [15] and Table S2), the possibility that the proteome could be correlated with the genetic background was tested by principal component analysis. Neither the four accessory gene regulator (agr) types nor the 21 clonal complexes (CC) and 2 sequence types (ST) of the collection explained the proteome distribution as no proteomic profile could be associated with any of these genetic backgrounds (Figure 3).…”
Section: Mrm Assay Development and Choice Of The Peptide Surrogatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the higher incidence of SSTI in children in PVL-endemic sub-Saharan Africa [ 13 , 21 ], it could be assumed that the immature humoral immunity of children lacks protective antibodies against PVL. Indeed, in a recent study on S. aureus pneumonia almost all cases in a patient cluster under the age of three were caused by PVL-positive S. aureus [ 22 ]. Nevertheless, Hermos et al [ 23 ] reported that antibody levels against PVL were significantly elevated in children with PVL-positive methicillin-resistant S. aureus (MRSA) SSTI compared to children infected with PVL-negative MRSA or to uninfected children.…”
Section: Discussionmentioning
confidence: 99%
“…Global data indicates an increasing trend of incidence and severity of SSTIs caused by MRSA isolates ( Olaniyi et al., 2017 ). Panton Valentine leukocidin (PVL) is a virulence factor which is associated with S. aureus strains causing SSTI and severe forms of community acquired pneumonia ( Gosbell, 2005 ; Wannet et al., 2005 ; Yamasaki et al., 2005 ; Marazza et al., 2007 ; Masiuk et al., 2010 ; Gillet et al., 2021 ). PVL consists of two distinct components which form polymeric pores in the membranes of white blood cells which leads to cell death.…”
Section: Introductionmentioning
confidence: 99%